2020
DOI: 10.1159/000505887
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Phenotypic Spectrum of Huntington Disease: Hypothermia

Abstract: Huntington disease (HD) is an autosomal dominant<b> </b>progressive neurodegenerative disorder associated with expanded CAG repeat size in the huntingtin gene and usually presenting with movement disorder, psychiatric symptoms, and cognitive decline. Sleep problems, weight loss, and cachexia are also common. Here, we report a patient presenting with hypothermia in late-stage HD. Although thermoregulatory defects were documented in animal models, this is the first report describing HD with hypotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Hypothermia has been reported in HD animal models 110 and in one patient in late-stage HD. 111 Thermoregulatory disorders in HD could be secondary to the involvement of the brown adipose tissue, skeletal muscle, or hypothalamus. 112 Brown adipose tissue has blunted heat production response of the mitochondrial uncoupling protein UCP1 to cold stimuli 113 in mouse models of HD.…”
Section: Review Thermoregulatory and Sweating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia has been reported in HD animal models 110 and in one patient in late-stage HD. 111 Thermoregulatory disorders in HD could be secondary to the involvement of the brown adipose tissue, skeletal muscle, or hypothalamus. 112 Brown adipose tissue has blunted heat production response of the mitochondrial uncoupling protein UCP1 to cold stimuli 113 in mouse models of HD.…”
Section: Review Thermoregulatory and Sweating Disordersmentioning
confidence: 99%
“…There is very limited data regarding thermoregulatory and sweating disorders in HD (Table 1). Hypothermia has been reported in HD animal models 110 and in one patient in late‐stage HD 111 …”
Section: Thermoregulatory and Sweating Disordersmentioning
confidence: 99%
“…Interestingly, N171-82Q HD mice, which are known to display reduced body temperatures starting at 120 days of age, have been shown to live longer when housed at a higher ambient temperature (30 • C instead of 20 • C) [83]. Of note, although hypothermia had only been documented in some HD animal models [83,84], a recent study has now reported a case of hypothermia in a 29-year-old HD patient, who presented to the emergency department with a body temperature of 34 • C (axillary) [87]. These findings emphasize the fact that regular pathways of thermoregulation (such as those involving PGC-1α) may also be disrupted in HD and deserve further investigation.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%